Ignacio Torres Giraldo and Political Languages in Colombia, 1893-1968 - Largo Vargas, Joan Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper examines Ignacio Torres Giraldo, a leftist leader who formed part of a singular intellectual context, marked by a certain openness and political, social and cultural transformations. The study of this writer and politicians’ personal archive and the reconstruction of the linguistic context in his works, in dialogue with elements of Cultural History and a new Political-Intellectual History, enable new interpretations on the meaning of this particular individual and his relation with the social and political context. Ignacio Torres Giraldo walked a difficult path, adapting his discourse to the political languages of a profoundly conservative country. We pose that the place occupied by the vital journey of Torres Giraldo is not coherent with his arguments or writing style, but responds to a capacity of agency constructed within the scarce and diffuse breaches left by the conservative intellectual tradition and its aversion to change.